The Effectiveness of the PQRST Model in Enhancing Scientific Literacy and Critical Thinking Skills of Students on the Topic of Human Excretory System in the Merdeka Curriculum Era - Arifah, Fina Nurul (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
This study investigates the effectiveness of the PQRST (Preview, Question, Read, Summarize, Test) model in enhancing scientific literacy and critical thinking skills among eleventh-grade students at SMAN 3 Kota Cirebon, particularly focusing on the human excretory system in the context of the Merdeka Curriculum. The research applied a quasi-experimental design with a pretest-posttest control group approach, involving 30 students from two classes. The experimental group received instruction using the PQRST model, while the control group followed conventional teaching methods. Results indicate significant improvements in the experimental group's scientific literacy across three aspects: context, knowledge, and competence. The normalized gain (N-Gain) scores were higher in the experimental group (0.72 for context, 0.77 for knowledge, and 0.71 for competence) compared to the control group. Statistical analysis revealed significant differences (p < 0.05) in all aspects of scientific literacy, confirming that the PQRST model significantly enhanced students' learning outcomes. Moreover, students reported positive responses towards the PQRST model, citing improved engagement, confidence, and critical thinking abilities. This study supports the goals of the Merdeka Curriculum in fostering independent, critical thinkers with strong scientific literacy. In conclusion, the PQRST model has proven to be an effective learning strategy to improve scientific literacy, critical thinking, and student engagement, which aligns with the objectives of the Merdeka Curriculum to produce globally competitive, literate students.